Strukturalisme sebagai Basis Ontologis untuk Ilmu Pendidikan - Moh. Gema Maulana (Papanda, 2025)
Motivated by Zongyi Deng's analysis of the persistent crisis in educational studies, this article aims to establish its fundamental ontological basis. Deng's work, building on Gert Biesta and Jim Hordern's contributions in the British Journal of Educational Studies (Volume 7, No. 5, 2023), sought to define a unique identity for education by drawing on German Pädagogik and Schwab's theory of the Practical. In contrast, this article proposes structuralism, specifically ontic structural realism, a school of thought from the philosophy of science, as the core foundation for educational studies. This approach is particularly effective in addressing the field's fragmentation and identity crisis by focusing on the underlying relational patterns and interdependencies constituting its unique ontological status, rather than viewing it as merely a collection of disparate parts. Structuralism posits that reality is best understood through the empirical scientific constructs of entities and their relationships, where structures determine the position of each element within a whole. This systematic literature review will extract data on how various disciplinary contributions are conceptualised and interrelate within educational studies. The article concludes that the traditional foundational disciplines are merely 'nodes' within the overarching structure of educational studies, which possesses its inherent ontological status.